Power Characterisation for Fine-Grain Reconfigurable Fabrics. (26th January 2010) - Becker, Tobias; Jamieson, Peter; Luk, Wayne; Cheung, Peter Y. K.; Rissa, Tero
Abstract : This paper proposes a benchmarking methodology for characterising the power consumption of the fine-grain fabric in reconfigurable architectures. This methodology is part of the GroundHog 2009 power benchmarking suite. It covers active and inactive power as well as advanced low-power modes. A method based on random number generators is adopted for comparing activity modes. We illustrate our approach using five field-programmable gate arrays (FPGAs) that span a range of process technologies: Xilinx Virtex-II Pro, Spartan-3E, Spartan-3AN, Virtex-5, and Silicon Blue iCE65. We find that, despite improvements through process technology and low-power modes, current devices need further improvements to be sufficiently power efficient for mobile applications. The Silicon Blue device demonstrates that performance can be traded off to achieve lower leakage.